Development and psychometric evaluation of a new tool for measuring the attitudes of patients with progressive neurological diseases to ethical aspects of end-of-life care - Bužgová, Radka (BMC Med Ethics, 2020)
BACKGROUND: Knowing the opinions of patients with Progressive Neurological Diseases (PNDs) and their family members on end-of-life care can help initiate communication and the drawing up of a care plan. The aim of this paper is to describe the creation and psychometric properties of the newly developed APND-EoLC questionnaire (the Attitudes of Patients with Progressive Neurological Disease to End of Life Care questionnaire). METHODS: Following focus group discussion, four main areas of interest were identified: patients’ and family members’ attitudes towards end-of-life care, factors influencing decisions about treatment to prolong patients’ life, concerns and fears regarding dying, and opinions on the system of care. The created questions were divided into domains based on factor analysis and psychometric properties were evaluated by sample of 209 patients with PND and 118 their family members. RESULTS: The final version of the scale contains a total of 28 questions divided into six domains (end-of-life control, keeping patients alive, trust in doctors/treatment, trust in social support, sense of suffering, and dependence/loss of control) and five individual questions determining views of the care system with specified response options. Construct validity was verified by confirmatory factor analysis for each evaluated area individually. Appropriate psychometric properties were identified in the questionnaire. CONCLUSIONS: The APND-EoLC questionnaire can be recommended for use in both research and clinical practice.